Mixed-Method Competency-Based Assessment Among Nurses In Region I, Philippines - Lacalle, Rainier C. Moreno (Journal of International Scholars Conference - ALLIED HEALTH, 2016)
The main purpose of this paper is to determine the competency level of nurses in Region I, Philippines as perceived by immediate superiors, patients, and themselves. Mixed-method was employed in this research. There were 58 nurses, 30 immediate superiors, and 4 informant patients included in this study. Four hospitals in Region I were randomly selected as the locale of the study. The study found out that most respondents are young, female, Roman Catholic, bachelors degree only, average board passers, and beginner in the profession. The level of competencies of nurses is competent (not excellent). Smiling, health education, and more patient contact need strengthening. Furthermore, educational attainment might result to the improvement of core competencies. Finally, this study found out strong interdependence between the core competencies safe and quality nursing care and ethico-moral responsibility as perceived by both the nurses and immediate superiors. Dichotomized relationship was found on the rest of the competencies.